The Effectiveness of the Team Games Tournament Model in Improving Motivation and Learning Outcomes in High School Music Education: A Quasi-Experimental Study - Indah Setyaningrum; Hafid Zuhdan Bahtiar; Ron Noriyah (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2025)
Objective: This study aims to explore and implement the Team Games Tournament (TGT) learning model in music learning at SMA Negeri 2 Mranggen. The TGT model, which is part of a cooperative learning strategy, is expected to increase active participation, collaboration between students, and conceptual understanding in music art learning. Method: This study uses a quantitative approach and a quasi-experimental research type. The sample in this study consists of three classes, namely class XI G, H and I. The sampling technique is purposive sampling. Data collection used includes tests, questionnaires, and observations. The instruments to be used include tests, questionnaires, and observation sheets. Data analysis techniques in this study with descriptive analysis, validity tests include expert validation and instrument trial validation, reliability tests, normality tests and t-tests. Results and Discussion: The results of the study showed that there was a significant increase in student learning outcomes, the initial validity value obtained a result of 0.254 or 25.4 included in the (Low) category and the final validity result obtained a result of 0.864 or 86.4 included in the (very high) category. From these results, it is known that the difference between the pretest and posttest results is 0.610 or 61.0 which indicates that the increase in student motivation and learning outcomes is in the high category. Conclusion: learning music arts with the use of the Team Games Tournament (TGT) learning model can increase student motivation and learning outcomes at SMA Negeri 2 Mranggen by 61.0. These findings provide a practical contribution to the development of active learning models in the context of arts education in secondary schools, especially in music learning, and open up opportunities for the application of similar models in other schools.